The Constitutional Court’s Authority in Judicial Review of the Notary Position Law: A Legal Review of Law No. 2 of 2014 Based on Theories of Justice and Legal Certainty - Hartono, Octafani Rheaeda; Rahayu, Mella Ismelina Farma (Universitas Islam Negeri Alauddin Makassar, 2026)
This study critically examines the authority of the Constitutional Court in conducting judicial review of Law No. 2 of 2014 on the Notary Position, analyzed through the perspectives of legal certainty and justice. Unlike previous studies that predominantly describe the Constitutional Court’s authority in general terms, this research specifically addresses the normative implications of Constitutional Court decisions on the regulation of the notary profession and the legal consequences arising therefrom. Employing a normative juridical method with statutory and case approaches, this study analyzes relevant legislation and several Constitutional Court decisions concerning the Notary Law. The findings reveal that while Constitutional Court decisions play a crucial role in safeguarding constitutional rights and providing legal certainty and justice for affected parties, they simultaneously expose a legal vacuum, particularly when granted petitions are not followed by adequate implementing regulations. This condition stems from the inherently passive nature of the Constitutional Court, which is constitutionally limited to reviewing laws without possessing legislative authority to formulate new norms. This study contributes theoretically by strengthening the discourse on the relationship between judicial review, legal certainty, and justice within the Indonesian constitutional system. Practically, it underscores the urgency of legislative responsiveness in addressing legal vacuums following Constitutional Court decisions to ensure the effective implementation of constitutional justice and prevent normative uncertainty in the regulation of notary positions.